2009
DOI: 10.1128/iai.00453-09
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Mediated Responses toCandida albicansin Mice Expressing the Human Immunodeficiency Virus Type 1 Transgene

Abstract: The critical impairments of innate and adaptive immunity that cause susceptibility to mucosal candidiasis in human immunodeficiency virus (HIV) infection have not been fully determined. We therefore conducted an analysis of macrophage-mediated responses to Candida albicans in transgenic (Tg) mice expressing Nef, Env, and Rev of HIV type 1 (HIV-1) in CD4 ؉ T cells, dendritic cells, and macrophages and developing an AIDS-like disease (CD4C/HIV MutA Tg mice). Macrophages were successfully recruited to the oral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
0
9
0
1
Order By: Relevance
“…Of these specific cell populations, only macrophages express the HIV-1 transgene (19) and would thus be susceptible primarily to altered cytokine expression. In this regard, we have previously shown that F4/80 ϩ macrophages recruited to the gastric submucosa and oral mucosa of HIV-1-expressing Tg mice in response to Candida albicans infection express the mannose receptor (CD206) almost uniformly, but MCP-1 only very infrequently (26), consistent with an alternatively activated (M2) phenotype known to be associated with susceptibility to cryptococcosis (36,52). Furthermore, because it has been shown that experimental depletion of CD4 ϩ and CD8 ϩ T cells independently abrogates the appearance of a protective inflammatory response to pulmonary C. neoformans infection and augments systemic dissemination (63)(64)(65), it is likely that the depletion of these T-cell populations in the Tg mice contributed to the reduced pulmonary inflammatory cell response to C. neoformans and the augmented systemic dissemination to the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these specific cell populations, only macrophages express the HIV-1 transgene (19) and would thus be susceptible primarily to altered cytokine expression. In this regard, we have previously shown that F4/80 ϩ macrophages recruited to the gastric submucosa and oral mucosa of HIV-1-expressing Tg mice in response to Candida albicans infection express the mannose receptor (CD206) almost uniformly, but MCP-1 only very infrequently (26), consistent with an alternatively activated (M2) phenotype known to be associated with susceptibility to cryptococcosis (36,52). Furthermore, because it has been shown that experimental depletion of CD4 ϩ and CD8 ϩ T cells independently abrogates the appearance of a protective inflammatory response to pulmonary C. neoformans infection and augments systemic dissemination (63)(64)(65), it is likely that the depletion of these T-cell populations in the Tg mice contributed to the reduced pulmonary inflammatory cell response to C. neoformans and the augmented systemic dissemination to the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diseases of the lung (lymphocytic interstitial pneumonitis), heart (myocytolysis and myocarditis), and kidney (tubulointerstitial nephritis, segmental glomerulosclerosis, and microcystic dilatation) develop in these Tg mice (19,24). Mucosal Candida infection in these Tg mice closely mimics the clinical and pathological features of candidal infection in human HIV infection (18,25) and has allowed us to perform controlled studies on the immunopathogenesis of mucosal candidiasis in HIV infection (26)(27)(28).…”
mentioning
confidence: 99%
“…And when the immunological response must be activated? The connections among some components of the immunological system are not well understood yet, however, recent progresses allow a contextualized view of the defence system 204 and its failure substantially collaborates for the susceptibility of the oral mucosa to candidiasis in HIV+ patients 125 .…”
Section: Immunological Defencementioning
confidence: 99%
“…The local response against Candida albicans is mediated by macrophages and polymorphonuclear leukocytes, which are more potent that the dendritic cells to kill Candida albicans 220 and play an important role in the innate immunological response 205 . Further, they stimulate the lymphocytary proliferation and the synthesis of related cytokines 17,336,125 .…”
Section: Oral Mucosa Invasionmentioning
confidence: 99%
“…O burst respiratório, compreende a produção das espécies reativas de oxigênio (EROs), ânion superóxido e peróxido de hidrogênio, e pela produção de peroxinitrito e seu intermediário óxido nitrico (NO) pelos macrófagos (GOUPIL et al, 2009). A produção desses compostos descritos acima é responsável tanto pela morte quanto pela inibição do crescimento de C. albicans por causarem quebra no DNA e produção de adultos de proteína e lipídios.…”
Section: O Sistema De Reconhecimento De Padrões Moleculares Associadounclassified